Climate sensitivity in the Anthropocene. (20th June 2013) - Previdi, M.; Liepert, B. G.; Peteet, D.; Hansen, J.; Beerling, D. J.; Broccoli, A. J.; Frolking, S.; Galloway, J. N.; Heimann, M.; Le Quéré, C.; Levitus, S.; Ramaswamy, V.
Abstract Climate sensitivity in its most basic form is defined as the equilibrium change in global surface temperature that occurs in response to a climate forcing, or externally imposed perturbation of the planetary energy balance. Within this general definition, several specific forms of climate sensitivity exist that differ in terms of the types of climate feedbacks they include. Based on evidence from Earth's history, we suggest here that the relevant form of climate sensitivity in the Anthropocene (e.g. from which to base future greenhouse gas (GHG) stabilization targets) is the Earth system sensitivity including fast feedbacks from changes in water vapour, natural aerosols, clouds and sea ice, slower surface albedo feedbacks from changes in continental ice sheets and vegetation, and climate–GHG feedbacks from changes in natural (land and ocean) carbon sinks. Traditionally, only fast feedbacks have been considered (with the other feedbacks either ignored or treated as forcing), which has led to estimates of the climate sensitivity for doubled CO2 concentrations of about 3°C. The 2×CO2 Earth system sensitivity is higher than this, being ∼4–6°C if the ice sheet/vegetation albedo feedback is included in addition to the fast feedbacks, and higher still if climate–GHG feedbacks are also included. The inclusion of climate–GHG feedbacks due to changes in the natural carbon sinks has the advantage of more directly linking anthropogenic GHG emissions with the ensuing global temperature increase, thus providing a truer indication of the climate sensitivity to human perturbations. The Earth system climate sensitivity is difficult to quantify due to the lack of palaeo‐analogues for the present‐day anthropogenic forcing, and the fact that ice sheet and climate–GHG feedbacks have yet to become globally significant in the Anthropocene. Furthermore, current models are unable to adequately simulate the physics of ice sheet decay and certain aspects of the natural carbon and nitrogen cycles. Obtaining quantitative estimates of the Earth system sensitivity is therefore a high priority for future work.